THE EFFECT OF FINANCIAL STATEMENTS DISCLOSURE ON FINANCIAL DISTRESS: A STUDY OF INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Zufrizal (RADJA PUBLIKA, 2022)
This study examines the effect of the disclosure of financial statements on financial distress in infrastructure companies listed on the Indonesia Stock Exchange for the 2014-2018 period. The research used secondary data obtained from annual reports and financial statements of 19 infrastructure companies. The research utilized a quantitative approach by employing logistic regression analysis to determine the effect of financial statement disclosure on financial distress. The study found that financial statement disclosure has a significant negative effect on financial distress. This finding implies that companies that disclose their financial statements adequately have a lower likelihood of experiencing financial distress. Therefore, companies should prioritize the timely and accurate disclosure of financial information to reduce the risk of financial distress.